Piracy in Southeast Asia New Trends, Issues and Responses - Raymond, Catherine Zara (2016)
Piracy has plagued the region of Southeast Asia for many centuries and continues to do so to the present day. Despite increased efforts by the regional countries to reduce the problem, pirate attacks take place on an alarmingly regular basis in what are some of the world’s most strategically important waterways. This paper will examine the phenomenon of piracy in Southeast Asia, in particular that which occurs in and around the waters of Indonesia and the Straits of Malacca. The trends which have emerged in recent years will be highlighted; specifically the types of attacks which take place, the different groups carrying out the attacks, the equipment they use and their targeting patterns. The study will then examine the causes of piracy, its impact and finally the responses of the region’s states to the problem.